Editorial: Advances in Liver Inflammation and Fibrosis due to Infectious Diseases - Oliveira, Sergio C. (2020)
Liver inflammation is a common trigger of hepatic disease, and it is considered the main driver of tissue damage (1). Although the liver is able to regenerate, chronic liver inflammation leads to tissue damage with concomitant fibrosis, frequently leading to cirrhosis, and carcinogenesis (2). The etiology of chronic liver inflammation may be infectious or not. Several microorganisms including bacteria, parasites, fungi, and virus could be involved...